2020
DOI: 10.3390/app10228220
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of Web News Archives for Crime Prediction

Abstract: In today’s world, security is the most prominent aspect which has been given higher priority. Despite the rapid growth and usage of digital devices, lucrative measurement of crimes in under-developing countries is still challenging. In this work, unstructural crime data (900 records) from the news archives of the previous eight years were extracted to predict the behavior of criminals’ networks and transform it into useful information using natural language processing (NLP). To estimate the next move of crimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
0
15
1
Order By: Relevance
“…The Linear regression and the long short term memory were combined to make the prison term prediction and the natural language processing techniques, such as the word embedding, were also used to improve the performance. Umair et al [79] transformed the spatio-temporal analysis into natural language processing scheme. The dataset used in this methods was the data crawled from the newspaper, such as the Dawn News, Dunya News, Ary News, The News, Daily Parkistan, Panistan Press Foundation, The Nation, and Journalism Pakistan by the Data Miner Tools.…”
Section: The Models Based On Different Media Typementioning
confidence: 99%
“…The Linear regression and the long short term memory were combined to make the prison term prediction and the natural language processing techniques, such as the word embedding, were also used to improve the performance. Umair et al [79] transformed the spatio-temporal analysis into natural language processing scheme. The dataset used in this methods was the data crawled from the newspaper, such as the Dawn News, Dunya News, Ary News, The News, Daily Parkistan, Panistan Press Foundation, The Nation, and Journalism Pakistan by the Data Miner Tools.…”
Section: The Models Based On Different Media Typementioning
confidence: 99%
“…The increasing amount of media information as newspapers and social media entries demand new ways of data processing, in a form of automation and specific machine learning algorithms that can be useful for criminology and crime prevention, constituting a new research frontier in this area (e.g., Umair et al, 2020).…”
Section: Caap and Media Archivesmentioning
confidence: 99%
“…Research is currently exploring new methods to work, for instance, with web news to handle a high volume of data streams (Za'in et al, 2017) to be able to make such data useful. As suggested by Umair et al (2020), there is a clear potential on this vast amount of information coming from archives to detect and predict crime locations but also predict patterns and transform them into useful information in crime prevention.…”
Section: Potentialitiesmentioning
confidence: 99%
“…964973. Research (Umair et al, 2020) uses data on crime in Pakistan, resulting in the conclusion that the accuracy of k-NN can reach a maximum of 92%, while the Random Forest algorithm can only reach 62%. The results showed that the higher the value of K, the better the k-NN algorithm, where for K values of 3, 5, 7, and 9 the k-NN algorithm has an accuracy rate of 89%, 93%, 93%, and 94% .…”
Section: Introductionmentioning
confidence: 99%